Efficacy and safety of paranasal sinus balloon catheter dilation in pediatric chronic rhinosinusitis: a systematic review - Ahmad A. Mirza; Hatim Y. Shawli; Talal A. Alandejani; Sattam M. Aljuaid; Mahmoud Alreefi; Razan A. Basonbul; Shahad K. Alhomaiani; Banan A. Althobaity; Dhuha A. Alhumaidi; Faisal Zawawi (Journal of Otolaryngology - Head and Neck Surgery, 2020)
Abstract Objective Chronic rhinosinusitis (CRS) negatively affects quality of life (QoL), and balloon catheter sinuplasty (BCS) has shown good outcomes in adult patients. However, there has not been much research on the effects of BCS on pediatric patients. The objective of this review is to systematically assess the literature for studies demonstrating the effectiveness and safety of BCS in pediatric CRS patients. Data sources PubMed, Embase and Cochrane Library. Study selection We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis recommendations (PRISMA) to conduct our study. Observational- and interventional-based studies reporting efficacy and/or side effects of BCS among pediatric populations were included. Efficacy was evaluated by clinically reliable measures including Sino-Nasal 5 (SN-5) QoL scale. Antibiotic usage and revision surgery were also evaluated. Data extraction Articles were screened, and data were obtained. Study design, sample size and demographics, treated sinuses, criteria of inclusion, adjunct procedure(s), follow-up time, and outcomes measured were reported. Main findings Out of 112 articles identified, 10 articles were included: two interventional controlled trials and eight observational studies. All studies evaluating QoL by SN-5 showed a remarkable reduction in SN-5 score postoperatively. Improvement in the computed tomography (CT) and endoscopic findings for up to 1 year after operation was reported. Furthermore, the majority of patinets treated with BCS did not recieve any course of sinusitis-indicated antibiotics during long-term follow-up, and they had low surgical revision rates. Minor side effects were reported, most commonly synechia. Conclusion Available evidence suggests that BCS is safe and effective for the treatment of CRS in pediatric patients. Future randomized controlled studies with large sample size are warranted. Such studies can further determine the efficacy of BCS in managing children with CRS.